The cat who saved the library - Natsukawa, Sōsuke, 1978-; Kawai, Louise Heal (London : Picador, 2025)
"A chronic asthma condition prevents thirteen-year-old Nanami from playing sports or spending time with her friends after school. But nothing can stop her from one of her favorite activities. Nanami loves to read and happily spends much of her free time in the library, cocooned among the stacks. Then one day, Nanami notices that, despite the library being as deserted as ever, some of her favorite books...are disappearing from the shelves. When she alerts the library staff, they dismiss her concerns...That's when Tiger, the talking tabby cat who saves books, comes to the rescue. Are Nanami and Tiger prepared to face the dangerous challenges that lie ahead? Why are faceless gray soldiers burning books in a stone castle?"--
How it all began -- The one who walks beside us -- The one who was created -- The one who proliferates -- The one who questions -- How it all ended.
"Originally published in Japan in 2024 by Shogakukan, Inc." -- Title page verso.
Japanese fiction Translations into English
Donated by Farhana Zahir (Assistant Professor, BBS, BRAC University)
Keywords: Teenage girls -- Fiction; Cats -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Lost articles -- Fiction; Animal fiction; Fantasy fiction; Magic realist fiction; Novels; Romans